The Muslim land-distribution practice in Malaysia and its implications on Maqasid-al-Shariah - Khalid, Haniza; Yusuf, Muhammad Dayyan (2012)
The Malays’ practice of distributing a deceased’s lands based on Faraid calculations under the framework of the Torrens land registration system has been partly blamed for the problem of land fragmentation and low land values prevalent in Malaysia today. Partitioning land according the entitlement of each beneficiary will result in uneconomic land sizes and farm operations, conversion of agricultural land to other uses (and hence, the subsequent decline of food production capabilities of the country as a whole) and ultimately the erosion of Malay-Muslim land ownership and economic wealth. All of these outcomes go against the concept of Maqasid-al-Shariah particularly with respect to preserving the Maal and income of the Muslims. This paper seeks to explore the land fragmentation issue as linked to the asset distribution practice amongst Malay-Muslims in Malaysia and subsequently propose a re-examination of the Malaysian practice of Shariah-based distribution vis-à-vis the existing land administration framework.